PENDAMPINGAN STRATEGI PEMASARAN DIGITAL UNTUK MENINGKATKAN PENJUALAN KEPADA PELAKU UMKM JAMU TRADISIONAL - Darulfadli, Iqbal; Fatimah, Dewi; Kuwartisen, Deri; Harpepen, Andi (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
The goal of this community service project is to strengthen UMKM's capacity to use digital marketing tactics, particularly social media, to boost sales. In the past, the traditional herbal medicine UMKM "Sari Minuman" lacked the knowledge and expertise to use digital platforms, which is the activity's aim. UMKM have gained expertise and experience in setting up business accounts, handling content, and utilizing digital marketing tools on Instagram and WhatsApp Business through the phases of observation, interviews, training, and hands-on support. The activity's outcomes demonstrated a notable rise in consumer interaction, market reach, and promotional activities. This exercise demonstrates how UMKM's professionalism and competitiveness in the digital age can be enhanced by a methodical approach to digital marketing support.